Prenatal diagnosis versus first-trimester screening of trisomy 21 among pregnant women aged 35 or more. (April 2015) - Ghi, Tullio; Arcangeli, Tiziana; Ravennati, Francesca; Salsi, Ginevra; Montaguti, Elisa; Pacella, Giuseppina; Maroni, Elisa; Pittalis, Maria Carla; Pompilii, Eva; Pilu, Gianluigi; Rizzo, Nicola
Abstract Objective: To compare the policy of prenatal diagnosis versus first trimester screening of trisomy 21 among pregnant women of advanced age. Methods: A retrospective study was conducted on patients aged ≥35 divided in two groups: patients who requested first trimester combined test and only in case of screen-positive result underwent invasive testing (group A); patients undergoing chorionic villous sampling or amniocentesis as first investigation (group B). The following outcome variables were compared: antenatal detection of trisomy 21, occurrence of trisomy 21 at birth, miscarriage rate, hospitals' costs. Results: 4527 women were included. Of these, 534 (11.80%) underwent T21 screening whereas 3993 (88.20%) requested primary invasive testing. In group A, 64 combined test were positive (11.99%) and 8 trisomy 21 cases were diagnosed (1.50%); the loss of euploid fetuses after invasive procedure was 4.55% (2/44). No false-negative case was observed. In group B 57 cases of trisomy 21 were diagnosed (1.43%), and pregnancy loss rate of chromosomally normal fetuses was 0.45% (17/3806). The estimated cost was, respectively, 67.720€ for the primary screening versus 1.996.500€ for direct prenatal diagnosis. Conclusion: First trimester screening of trisomy 21 is highly accurate and cost saving among women ≥35.